Prevalence, Mechanism, Genetic Diversity, and Cross-Resistance Patterns of Methicillin-Resistant Staphylococcus Isolated from Companion Animal Clinical Samples Submitted to a Veterinary Diagnostic Laboratory in the Midwestern United States - Mehmet Cemal Adiguzel; Kayla Schaefer; Trevor Rodriguez; Jessica Ortiz; Orhan Sahin (MDPI AG, 2022)
Methicillin-resistant Staphylococcus (MRS) is a leading cause of skin and soft tissue infections in companion animals, with limited treatment options available due to the frequent cross-resistance of MRS to other antibiotics. In this study, we report the prevalence, species distribution, genetic diversity, resistance mechanism and cross-resistance patterns of MRS isolated from companion animal (mostly dog and cat) clinical cases submitted to Iowa State University Veterinary Diagnostic Laboratory (ISU VDL) between 2012 and 2019. The majority of isolates were identified as Staphylococcus pseudintermedius (68.3%; 2379/3482) and coagulase-negative Staphylococcus (CoNS) (24.6%; 857/3482), of which 23.9% and 40.5% were phenotypically resistant to methicillin, respectively. Cross resistance to other β-lactams (and to a lesser extent to non-β-lactams) was common in both methicillin-resistant S. pseudintermedius (MRSP) and CoNS (MRCoNS), especially when oxacillin MIC was ≥4 μg/mL (vs. ≥0.5-<4 μg/mL). The PBP2a protein was detected by agglutination in 94.6% (521/551) MRSP and 64.3% (146/227) MRCoNS. A further analysis of 31 PBP2a-negative MRS isolates (all but one MRCoNS) indicated that 11 were mecA gene-positive while 20 were negative for mecA and other mec genes by PCR. The resistance to last-resort anti-staphylococcal human drugs (e.g., tigecycline, linezolid, vancomycin) among the MRS tested was none to very low. Even though genotyping indicated an overall high level of genetic diversity (87 unique PFGE patterns and 20 MLST types) among a subset of MRSP isolates tested (n = 106), certain genotypes were detected from epidemiologically connected cases at the same or different time points, suggesting persistence and/or nosocomial transmission. These results indicate a relatively high prevalence of MRS from companion animals in the Midwestern US; therefore, it is important to perform routine susceptibility testing of Staphylococcus in veterinary clinical settings for the selection of appropriate antimicrobial therapy.